2020
DOI: 10.1155/2020/6784512
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Physiological Relaxation Induced by Nature-Working with Ornamental Plants

Abstract: Objective. Nature has a significant impact on general well-being. However, till date, little psychophysiological evidence is available on the benefits of nature-based activities in adults. The primary goal of this study was to determine the physiological and psychological benefits of horticultural activity in adults. The participants were instructed to perform the making of a flower basket (horticultural activity) and a computer task (i.e., control activity) was compared. Methods. A total of 40 Chinese females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…This finding is consistent with that of Kim et al (2016) , who reported dramatically increased alpha waves after participants smelled an aromatic extract of orchid petals. Given the apparent connections between alpha wave power and relaxation ( Hassan et al, 2018a ; Tao et al, 2020 ), our findings, while preliminary, suggest that smelling fragrant Primula plants may have had a stronger restorative effect on participants than smelling non-fragrant Primula plants. Therefore, one of the suggestions of this result is to use fragrant flowers in places that need to create a relaxing atmosphere, such as studios, living rooms, hospitals, and so on.…”
Section: Discussionmentioning
confidence: 57%
“…This finding is consistent with that of Kim et al (2016) , who reported dramatically increased alpha waves after participants smelled an aromatic extract of orchid petals. Given the apparent connections between alpha wave power and relaxation ( Hassan et al, 2018a ; Tao et al, 2020 ), our findings, while preliminary, suggest that smelling fragrant Primula plants may have had a stronger restorative effect on participants than smelling non-fragrant Primula plants. Therefore, one of the suggestions of this result is to use fragrant flowers in places that need to create a relaxing atmosphere, such as studios, living rooms, hospitals, and so on.…”
Section: Discussionmentioning
confidence: 57%
“…Working with plants has been shown to reduce anxiety (Hassan et al, 2019). Tao et al (2020) reported that the anxiety index of adults decreased when performing horticultural activities compared with that when performing computer tasks. Shao et al (2020) compared engagement in horticultural activities and smartphone games performed by children and reported that the parasympathetic nerves increased during horticultural activities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the psychological stress experienced by the inhabitants is related to the negative feelings caused by crowded conditions [ 7 ]. Interpersonal proximity leads to more social interaction, a significant factor in generating psychological stress [ 8 ]. Lack of privacy caused by close distance causes anxiety [ 9 ].…”
Section: Introductionmentioning
confidence: 99%